2016
DOI: 10.1002/bjs.10424
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of lower perioperative blood glucose target levels for reduction of surgical-site infection

Abstract: Background: There is a clear association between hyperglycaemia and surgical-site infection (SSI). Intensive glucose control may involve a risk of hypoglycaemia, which in turn results in potentially severe complications. A systematic review was undertaken of studies comparing intensive versus conventional glucose control protocols in relation to reduction of SSI and other outcomes, including hypoglycaemia, mortality and stroke.Methods: PubMed, Embase, CENTRAL, CINAHL and WHO databases from 1 January 1990 to 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 58 publications
3
91
0
Order By: Relevance
“…reported that a glucose level >140 mg/dL was the only significant risk factor associated with SSI in patients undergoing colorectal surgery. Meta‐analysis23 confirmed the benefits of an intensive protocol targeting <150 mg/dL for reducing SSI, and recent guidelines7 recommended that perioperative glycemic control should be between 110 and 150 mg/dL. A dose–response relationship between BG level and SSI rate was reported in general surgery patients 14.…”
Section: Relationship Between Perioperative Bg and Ssi In Patients Whmentioning
confidence: 88%
See 4 more Smart Citations
“…reported that a glucose level >140 mg/dL was the only significant risk factor associated with SSI in patients undergoing colorectal surgery. Meta‐analysis23 confirmed the benefits of an intensive protocol targeting <150 mg/dL for reducing SSI, and recent guidelines7 recommended that perioperative glycemic control should be between 110 and 150 mg/dL. A dose–response relationship between BG level and SSI rate was reported in general surgery patients 14.…”
Section: Relationship Between Perioperative Bg and Ssi In Patients Whmentioning
confidence: 88%
“…Although a higher risk of hypoglycemic events was observed with the intensive protocol, the protocol including a very strict control group did not increase the risk of postoperative death and stroke compared with the conventional protocol in surgical patients,23 and it was concluded that an intensive protocol can be carried out safely without the risk of serious adverse events in surgical patients (Table 2). The result of this meta‐analysis, however, should be interpreted with caution.…”
Section: Indication For Intensive Protocol In Critically Ill Patientsmentioning
confidence: 97%
See 3 more Smart Citations